Sequelae of obstructive Nephropathy due to urolithiasis: a retrospective study at a tertiary care hospital of Lahore - Usama Muhammad Kathia; Ali, Azfar; Sheraz, Muhammad; Qadri, Haseeb Mehmood; Butt, Ali Imran; Gondal, Khizar Hayat (Journal of the Pakistan Medical Association, 2025)
The retrospective, observational study was planned to present the clinical manifestations of obstructive nephropathy secondary to urolithiasis, and its effect on long-term renal function. The sample comprised patients diagnosed with obstructive nephropathy secondary to stones admitted to the Department of Urology and Renal Transplant, Lahore General Hospital, Lahore, Pakistan, between January 1, 2018, and December 31, 2021. Data was analysed using SPSS 20. Of the 76 patients with a mean age of 50.06±13.42 years, 56(73.7%) were males and 20(26.3%) were females. The most frequent clinical cause was bilateral ureteric obstruction in 39 (51.3%) patients. The most common emergency procedure performed was unilateral percutaneous nephrostomy. It took an average of 10.8±2.3 days for patients to have a nadir value of creatinine. On follow-up, diabetes, presence of lower urinary tract symptoms and a higher value of creatinine at admission were significantly related to poorer outcomes (p<0.05). Keywords: Urolithiasis, Quackery, percutaneous nephrostomy.